NRDR Inhibits the Migration of Endometrial Cancer Cells and Affects Their Gene Expression - Ying Liu; Jiankai Shi; Shuxin Li; Shujun Liu; Yang Liu; Jiwei Liu; Xiaoying He; Chuncheng Liu; Libing Ma (Scientifica, 2025)
Conclusions: In our study, it turns out that NRDR is a tumor suppressor in endometrial cancer cells. Through investigating the physiological function and molecular mechanism of NRDR in endometrial cancer, our experiment provides a theoretical basis for further understanding the pathogenesis of endometrial cancer.